The practice of good governance in Zakat management: a holistic and comprehensive approach towards Zakat collection and distribution - Mohammad, Habibullah; Md, Atiullah (IIUM Institute of Islamic Banking and Finance (IIiBF), 2022)
Abstract: The purpose of this paper is to provide a general exposition on the concept of good governance of zakat, applying its management as an important panacea in today’s prevalent situation of financial calamity. The objective of this paper is to analyze the implication of good governance on zakat management as it is a pre-requisite for a well-organized society. Good governance dictates a set of policies to promote broad based economic growth, a dynamic private sector and social policies that will be directed towards zakat management. Seen from the Islamic point of view, careful application of good governance is vital to maximize economic and social advancement. Islam is a comprehensive code of life, and it provides guidelines for social, political, and economic systems. Hence, Islam concerns itself for collecting zakat and providing a decent life to its entire people through a prolonged welfare scheme that is essential for all Muslims. Subsequently, Islam needs rulers to prevent a drop in the standard of living of their subjects, thus they must concern themselves with stabilizing their economy and assuring constant economic growth. Therefore, good governance is to deliver and apply the regulation and duties in the best manner. The goal of Islamic good governance system is to eliminate corruption from the society and implementations of social justice as well as welfare of the people as the Shari’ah emphasizes the fair dealings in every aspect of life and observe justice to the masses. The methods of data collection are involved library research through reading and content analysis of primary and secondary sources.